Assessment of progress towards 20-20-20 targets: Evidence from Baltic States - Dalia Štreimikienė (Contemporary Economics, 2022)
The 2020 climate and energy package adopted in 2009 sets three key targets for EU Member States: 20% cut in greenhouse gas emissions (from 1990 levels); to ensure 20% of renewables in final energy consumption and to achieve 20% improvement in energy efficiency from 2005 levels. The paper analyses the progress of selected countries in achieving climate and energy targets by 2020. Baltic States, namely Lithuania, Latvia, and Estonia were selected for comparative assessment of their achievements in GHG emission reduction, energy efficiency improvement and use of renewable energy sources. Indicator's framework was constructed to capture the most important drivers of GHG emission reduction from fuel combustion. These indicators allow to compare countries in their achievements by assessing their main energy and climate change policies. The analysis and comparison of the trends of the main indicators allows to define the best performing country and the reason of this. Policy implications were developed for Baltic States to pursue further progress in achieving energy and climate targets for 2030 and 2050.
Keywords: H30; P18; Q20; Q30; 330; Renewable energy; energy efficiency; greenhouse gas emissions; energy and climate targets; policies; Baltic States